Staggered price contracts and inflation persistence: some general results - Karl Whelan (European Central Bank (ECB), 2004)
Despite their popularity as theoretical tools for illustrating the effects of nominal rigidities, some have questioned whether models based on Taylor-style staggered contracts can match the persistence of the empirical inflation process. This paper presents some general theoretical results about Taylor-style models. It is shown that these models do not have a problem matching high autocorrelations for inflation. However, they fail to explain a key feature of reduced-form Phillips-curve regressions: The positive dependence of inflation on its own lags. It is shown that staggered price contracting models instead predict that the coefficients on these lag terms should be negative.
Keywords: E31; 330; Inflation persistence; staggered contracts